Coumarins and chromanones from two Calophyllum species and their bioactivities - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher; Mohamed Zulkifli, Razauden (2016)

(untitled)
Calophyllum is a pan-tropical genus belongs to the Guttiferae family and locally known by Malay local folks as'bintangor'. There has been a continrnl interest to further investigate the phytochemicals of Calophyllurn species since this genus is a rich source of active secondary metabolites which showed anti-HIV, cytotoxicity and antimicrobial properties. In this study, phytochemicals studies on the barks and leaves of Calophyllum symingtonianum M. R. Henderson & Wyatt-Smith and Calophyllum ferrugineum Ridley were carried out. Cold extraction method was employed by using dichloromethane, ethyl acetate and methanol to give the respective crude exracts. Three counurins known as inophyllum D, inophyllum H and calanone as well as a chronranone known as isocordateoblongic acid were isolated from the dichloromethane extract of C. symingtoniotum. Another two chromanones identified as apetalic acid and isoapetalic acid were yielded from dichloromethane extract from barks of C. ferrugineum. The structures were elucidated by spectral analysis including NMR and MS. All compounds were tested for their antibacterial, cytotoxic and alpha-glucosidase inhibition activities. All chromanones moderately inhibited the growth of Gram positive bacteria, B. subtilis and S. outeus with MIC value in the range of 3l .25 - 125 mcg/mL. Inophyllum H was forurd to be cytotoxic towards MCF-7 (IC50 25.26 pgmL) and 4-549 (IC50 26.41 pgml) cancer cell lines. Inophyllum D showed the strongest a-glucosidase inhibition with ICso 35.7 microM, followed by inophyllum H (ICso 62.30 microM) and calanone (IC50 > 100 microM).